Traumatised youth harbour feelings of revenge: investigating the association between PTSD symptomatology, vengeance, and willingness to forgive among the Congolese adolescent refugees in Uganda - Ainamani, Herbert E.; Rukundo, Godfrey; Gumisirizaa, Nolbert; Tumwine, Christopher; Hall, Jonathan (EUROPEAN JOURNAL OF PSYCHOTRAUMATOLOGY, 2024)
Background: Prolonged conflicts in the Democratic Republic of Congo (DRC) have caused widespread psychological trauma among civilians leading to maladaptive coping strategies across generations. Despite this occurrence, empirical studies on the prevalence of trauma and its impact on attitudes towards revenge and forgiveness, particularly among the youth, are scarce. This study aims to clarify the relationship between Post Traumatic Stress Disorder (PTSD) symptom severity and the desires for forgiveness and revenge among Congolese adolescents residing in Uganda. Methods: We analysed data from 269 adolescent refugees from the DRC living in the Nakivale refugee settlement in Southwestern Uganda. The assessment included exposure to war-related traumatic events and the MINI-KID for DSM-V PTSD symptom severity. The Heartland Forgiveness and Vengeance Scales measured willingness to forgive and feelings of vengeance. Results: Exposure to war-related traumatic events was notably high in our sample, with severe deprivation of food (260 [97%]), exposure to armed combat (249 [93%]), witnessing bombing, burning, or destruction of houses (245 [91%]), disappearance of family members (239 [89%]), and seeing dead bodies (236 [88%]). PTSD symptom severity was negatively associated with willingness to forgive (b = −0.48; 95% CI −0.71–−0.25; p < .001) and positively associated with vengeance (b = 0.18; 95% CI 0.04–0.32; p = .011). Conclusion: PTSD symptom severity reduces the willingness to forgive and increases the desire for vengeance among adolescent refugees. Mental health clinicians and policymakers should consider addressing maladaptive coping behaviours related to feelings of revenge and unwillingness to forgive in their support strategies for refugees
Keywords: Adolescent; Refugees; PTSD symptom severity; Vengeance; Forgiveness; Uganda